2020
DOI: 10.2196/24531
|View full text |Cite
|
Sign up to set email alerts
|

People’s Experiences and Satisfaction With Telehealth During the COVID-19 Pandemic in Australia: Cross-Sectional Survey Study

Abstract: Background In response to the COVID-19 pandemic, telehealth has rapidly been adopted to deliver health care services around the world. To date, studies have not compared people’s experiences with telehealth services during the pandemic in Australia to their experiences with traditional in-person visits. Objective This study aimed to compare participants’ perceptions of telehealth consults to their perceptions of traditional in-person visits and investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
178
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(236 citation statements)
references
References 22 publications
33
178
2
2
Order By: Relevance
“…The data show that the majority of the respondents (90%) were satisfied or very satisfied with the help or treatment they received via phone, email, chat, or video services, as the process was easy to manage and worked well. These findings are in line with previous research reporting high satisfaction rates with the use of telehealth during the COVID-19 pandemic in different settings, for example in the context of gastroenterology [ 22 ] and epilepsy patients [ 23 ] in the United States, or among Australian adults [ 24 ]. Moreover, high satisfaction with the use of telehealth was also observed in earlier studies prior to the COVID-19 pandemic [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…The data show that the majority of the respondents (90%) were satisfied or very satisfied with the help or treatment they received via phone, email, chat, or video services, as the process was easy to manage and worked well. These findings are in line with previous research reporting high satisfaction rates with the use of telehealth during the COVID-19 pandemic in different settings, for example in the context of gastroenterology [ 22 ] and epilepsy patients [ 23 ] in the United States, or among Australian adults [ 24 ]. Moreover, high satisfaction with the use of telehealth was also observed in earlier studies prior to the COVID-19 pandemic [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…According to the same survey "almost half (49%) reported they were likely to use telehealth services in the future." A separate national study of people's experiences and satisfaction with telehealth during the COVID-19 pandemic in Australia by Isautier et al (22) found that "telehealth appointments were reported to be comparable to traditional in-person medical appointments by most of our sample (p. 2).…”
Section: Australian Responses To Covid-19 Pandemicmentioning
confidence: 65%
“…It should be added that an earlier study performed in a representative sample of the Polish population suggested that attitudes to key public health interventions were related to the level of HL but not eHL (measured with Pl-eHEALS) [95]. Furthermore, eHL was not a significant predictor of the quality of telehealth experience during the COVID-19 pandemic in the sample of patients from Australia [96]. In agreement with the findings described in our paper, Kubb & Foran did not observe a meaningful contribution of eHL to a parent's change of stress level when searching the web for current somatic health issues related to their own or their children's symptoms [97].…”
Section: Discussionmentioning
confidence: 87%